Aspectos práticos da estereotomografia - LIMA, Isabela Coelho (2019)
The construction of a velocity-depth model is an essential step for imaging complex structures. One of the tecniques used to obtain this model is stereotomography, a tomographic method based on the concept that locally coherent events provide information about velocity models. Di erently from tradional tomography, stereotomography uses the horizontal components of slowness as data for inversion. Moreover, it calculates, additionally to the velocity model, a pair of ray segments that originates in the same point in depth. As any other inverse method, stereotomography aims at nding the model parameters that best t the selected data. The mathematical problem is non-linear, and it's solution is available through linear iterations. The convergence of the algorithm depend strongly on the initial model. In the original implementation of stereotomography, the initial velocity model should be given by the user, while the initial ray parameters are computed in an homogeneous model. This work extended the original algorithm by adding a new strategy for obtaining the initial ray parameters, which are calculated through ray tracing in an arbitrary velocity model. With this new source code, the in uence of the initial model in stereotomography was evaluated. The new strategy produced acceptable data mis ts in all tests. When using the models resulting from time-to-depth convertion, the implemented tecnique produced better results than the original one. This work also evaluated the in uence of the data scaling on the convergence of the algorithm. The appropriate choice of scales is essencial for obtaining satisfatory data mis ts.